THE CORRELATION BETWEEN STUDENTS' SELF-EFFICACY AND SPEAKING PERFORMANCE OF VOCATIONAL HIGH SCHOOL - Zahwa Aulia; Nur Fauzia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to examine the correlation between students’ self-efficacy and their speaking performance among eleventh-grade students of a vocational high school in Surabaya. This research employed a quantitative approach using a correlational research design. The participants consisted of 95 eleventh-grade students selected through a random sampling technique. The data were collected using two research instruments: a Speaking Skills Self-Efficacy Beliefs (SSSEB) questionnaire adapted from Asakereh and Dehghannezhad (2015) and a speaking performance test in the form of a descriptive text presentation. Students’ speaking performance was assessed based on five components, namely pronunciation, grammar, vocabulary, fluency, and comprehension. The data were analyzed using IBM SPSS Statistics version 25. Descriptive statistical analysis was conducted to describe the levels of students’ self-efficacy and speaking performance. The Kolmogorov–Smirnov normality test indicated that the data were not normally distributed; therefore, Spearman’s rank correlation was employed to determine the relationship between the variables. The results revealed a moderate and statistically significant positive correlation between students’ self-efficacy and their speaking performance (ρ = 0.536, p < 0.05). This finding indicates that students who possess higher levels of self-efficacy tend to demonstrate better speaking performance. In conclusion, students’ self-efficacy is significantly correlated with their speaking performance. Thus, enhancing students’ self-efficacy is considered an important factor in improving their speaking ability. It is recommended that English teachers implement instructional strategies that foster students’ confidence, motivation, and active engagement in speaking activities.